2020
DOI: 10.7717/peerj.8930
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis revealed key prognostic genes and microRNAs in hepatocellular carcinoma

Abstract: Background. Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide. However, the molecular mechanisms involved in HCC remain unclear and are in urgent need of elucidation. Therefore, we sought to identify biomarkers in the prognosis of HCC through an integrated bioinformatics analysis. Methods. Messenger RNA (mRNA) expression profiles were obtained from the Gene Expression Omnibus database and The Cancer Genome Atlas-Liver Hepatocellular Carcinoma (TCGA-LIHC) for the screening of common dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 53 publications
(24 reference statements)
1
24
0
Order By: Relevance
“…Current researchers are focusing on personalized treatment based on the multi-gene assays ( Pan et al, 2019 ). With the continuous development of high-throughput sequencing technology, bioinformatics analysis plays a key role in the diagnosis, prognosis and screening of tumors ( Goldfeder et al, 2017 ; Ma, Zhou & Zheng, 2020 ). Many genes have been identified as signatures for diagnosis and prognosis of triple negative breast cancer ( Dai et al, 2019 ; Stovgaard et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Current researchers are focusing on personalized treatment based on the multi-gene assays ( Pan et al, 2019 ). With the continuous development of high-throughput sequencing technology, bioinformatics analysis plays a key role in the diagnosis, prognosis and screening of tumors ( Goldfeder et al, 2017 ; Ma, Zhou & Zheng, 2020 ). Many genes have been identified as signatures for diagnosis and prognosis of triple negative breast cancer ( Dai et al, 2019 ; Stovgaard et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A high CYP2E1 expression and activity may be a risk factor for HCC induced by diethylnitrosamine [50]. Downregulated CYP2E1 is regarded as a candidate prognostic biomarker in HCC [51]. Few reports are available concerning CYP2J2 expression in patients with HCC; CYP2J2 overexpression remarkably promotes the proliferation of HepG2 cells and affects the resistance to antitumor agents [52].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xie et al, 8 analyzed four Gene Expression Omnibus (GEO) datasets including GSE19665, GSE55092, GSE94660, and GSE121248 and identified key genes and pathways involved in HBVrelated HCC. 8 Ma et al, 9 obtained the mRNA expression profiles from the GEO database and the Cancer Genome Atlas-Liver Hepatocellular Carcinoma database, and the results showed that eleven hub genes with the most interactions were suggested as potential biomarkers in HCC. 9 Yan et al, 10 conducted a comprehensive study on bioinformatics, clinical analysis and in vitro validation and found that Misato family member 2, pseudogene had significant diagnostic and prognostic value in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…8 Ma et al, 9 obtained the mRNA expression profiles from the GEO database and the Cancer Genome Atlas-Liver Hepatocellular Carcinoma database, and the results showed that eleven hub genes with the most interactions were suggested as potential biomarkers in HCC. 9 Yan et al, 10 conducted a comprehensive study on bioinformatics, clinical analysis and in vitro validation and found that Misato family member 2, pseudogene had significant diagnostic and prognostic value in HCC. 10 Due to the rapid increase in the number of microarray datasets, the analysis of these datasets has not been sufficient.…”
Section: Introductionmentioning
confidence: 99%